1996
DOI: 10.21836/pem19960308
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the bacterial flora of faeces taken from foals, from birth to twelve weeks. Effect of the oral administration of a commercial colostrum replacer

Abstract: Preliminary studies on the bacterial flora of faeces taken from foals, from birth to twelve weeks. Effect of the oral administration of a commercial colostrum replacer. The faecal microflora of 18 normal, two month-old foals was composed of aerobes and facultative anaerobes, mainly Enterococci (107 CFIJ/g of faeces) and Lactobacilli (103 CFU/g) and strict anaerobes, cellulolytic bacteria (105 CFU/g) and Clostndia (104 CFU/g). At this early age ditferent bacterial stralns colonized the gut according to a specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 6 publications
4
13
0
Order By: Relevance
“…In parallel with the enhancement of forage intake rich in complex parietal carbohydrates, we observed the establishment of fibrolytic bacteria, as in the rumen of lambs (56) . In accordance with previous data in foal faeces (13) and lamb rumen (58) , cellulolytic bacteria first appeared at d2 and increased progressively, reaching stable values at d30. From the second week of life, the molar proportion of acetate and the ratio (acetate þ propionate): butyrate increased.…”
Section: Establishment Of the Bacterial Carbohydrate-degrading Capacisupporting
confidence: 92%
“…In parallel with the enhancement of forage intake rich in complex parietal carbohydrates, we observed the establishment of fibrolytic bacteria, as in the rumen of lambs (56) . In accordance with previous data in foal faeces (13) and lamb rumen (58) , cellulolytic bacteria first appeared at d2 and increased progressively, reaching stable values at d30. From the second week of life, the molar proportion of acetate and the ratio (acetate þ propionate): butyrate increased.…”
Section: Establishment Of the Bacterial Carbohydrate-degrading Capacisupporting
confidence: 92%
“…Regarding the length of our experiments, an hypothesis was that the increasing age of horses, as well as the season, could interfere with the effect of training. Age probably influences digestion either in very young (Cymbaluk et al 1989;Julliand et al 1996;Yuyama et al 2004;Ringler et al 2009) or mature horses, more than 20-years-old (Ralston et al 1989). In mature horses, such an hypothesis has not been demonstrated and is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Age probably influences digestion either in very young (Cymbaluk et al . 1989; Julliand et al . 1996; Yuyama et al .…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacilli, enterococci, and clostridia were isolated from feces as early as 3 d post parturition. Enrichments of cellulolytic and lactic acid bacteria indicated that these guilds were present in feces at levels similar to mature horses by 12 weeks [22].…”
Section: Introductionmentioning
confidence: 95%